Developing an infection prevention and control intervention to reduce hospital-acquired infections in Cambodia and Lao People’s Democratic Republic: the HAI-PC study protocol - Oy, Sreymom; Saing, Chan Hang; Ung, Mengieng; Zahari, Marina; Nouhak, Inthavong; Kim, Sothea; Nagashima-Hayashi, Michiko; Khuon, Dyna; Koy, Virya; Mam, Sovatha; Sayasone, Somphou; Saphonn, Vonthanak; et al. (Frontiers in Public Health, 2023)
Background: Hospital-acquired infections (HAIs) are significant public health issues, especially in low- and middle-income countries (LMICs). Hand hygiene and low-level disinfection of equipment practices among healthcare workers are some of the essential measures to reduce HAIs. Various infection prevention and control (IPC) interventions to reduce HAI incidence have been developed. However, effective interventions have not been well developed in the LMICs context. Therefore, this protocol aims to develop, pilot, and assess the feasibility and acceptability of an IPC intervention in Cambodia and the Lao People’s Democratic Republic (Lao PDR). Methods: This study will consist of four phases guided by the Medical Research Council (MRC) Framework. Three hospitals will be purposely selected – each from the district, provincial, and national levels – in each country. The gap analysis will be conducted in Phase 1 to explore IPC practices among healthcare workers at each hospital through desk reviews, direct observation of hand hygiene and low-level disinfection of equipment practices, in-depth interviews with healthcare workers, and key informant interviews with stakeholders. In Phase 2, an IPC intervention will be developed based on the results of Phase 1 and interventions selected from a systematic literature review of IPC interventions in LMICs. In Phase 3, the developed intervention will be piloted in the hospitals chosen in Phase 1. In Phase 4, the feasibility and acceptability of the developed intervention will be assessed among healthcare workers and representatives at the selected hospitals. National consultative workshops in both countries will be conducted to validate the developed intervention with the national technical working groups. Discussion: The MRC Framework will be employed to develop and evaluate an intervention to reduce HAIs in two LMICs. This theoretical framework will be used to explore the factors influencing hand hygiene compliance among healthcare workers. The gap analysis results will allow us to develop a comprehensive IPC intervention to reduce HAI incidence in Cambodia and Lao PDR. Findings from this protocol will feed into promising IPC interventions to reduce HAI incidence in other resource-limited settings.